2020
DOI: 10.13057/biodiv/d220121
|View full text |Cite
|
Sign up to set email alerts
|

Procruste analysis of forewing shape in two endemic honeybee subspecies Apis mellifera intermissa and A. m. sahariensis from the Northwest of Algeria

Abstract: Abstract. Abed F, Bachir-Bouiadjra B, Dahloum L, Yakubu A, Haddad A, Homrani A. 2021. Procruste analysis of forewing shape in two endemic honeybee subspecies Apis mellifera intermissa and A. m. sahariensis from the Northwest of Algeria. Biodiversitas 22: 154-164. Honey bees play an important role as pollinators of many crops. Thus they are collectively considered as a veritable economic source. The present study was undertaken to describe variation in the right forewing geometry in two Algerian honeybee subspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…The same result was also mentioned by Cornuet et al [ 14 ], indicating a gradient of mean body size that increases south to north. However, this was not confirmed in other studies related to wing size [ 5 , 6 , 9 ]; in one study the opposite relationship was even reported [ 8 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The same result was also mentioned by Cornuet et al [ 14 ], indicating a gradient of mean body size that increases south to north. However, this was not confirmed in other studies related to wing size [ 5 , 6 , 9 ]; in one study the opposite relationship was even reported [ 8 ].…”
Section: Discussionmentioning
confidence: 58%
“…When the shape of wing venation was analysed by geometric morphometrics, significant differences were found between A. m. sahariensis and other subspecies. However, a similarity to A. m. intermissa is also clearly visible and in some studies, a relatively large overlap was found between the two subspecies [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 87%
“…It has been established by previous studies that the two Algerian subspecies ( A. m. intermissa and A. m. sahariensis ) can be differentiated based on morphological and behavioural differences [ 6 ] and by mitochondrial, microsatellites and sequencing analyses [ 13 17 ]. Our sampling for this study includes both subspecies, although in a rather unbalanced way (16 sahariensis vs. 86 intermissa ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out to characterize the two subspecies according to morphological and molecular aspects. The morphometric studies undertaken on Algerian honey bees have shown the existence of two distinct subspecies that morphologically correspond to A. m. intermissa and A. m. sahariensis [ 13 15 ]. Several molecular studies have been conducted on Algerian bees notably with microsatellite markers [ 16 ] and a single A.m. intermissa individual was sequenced [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of techniques describing pig morphometric have been utilized in the past (Muta et al, 2011;Adeola et al, 2013;Walugembe et al, 2014). However, multivariate principal component and discriminant analyses, which have been successfully used in other livestock species (Yakubu et al, 2010;Fraga et al, 2016;Belkhadem et al, 2019;Mediouni et al, 2020;Meka et al, 2021;Abed et al, 2021) could be invaluable refined techniques for obtaining very useful information related to several characteristics of pigs (Ventura et al, 2012) including body measurements (Silva Filha et al, 2010) and thermo physiological traits. Evaluating and assessing the body weight, morphometric and heat-tolerance traits of animals are important to identify the uniqueness of populations, adaptive capacity and possible gene flow between the indigenous populations.…”
Section: Introductionmentioning
confidence: 99%